Sobre o brincar e os jogos teatrais no ensino fundamental: movimentos de dentro e de fora - Souza, Fernanda Antunes de (Universidade Federal de São Carlos, 2020)
The object of this work was born from my experiences as an educator in the early years of elementary school in a private school in the city of Sorocaba / SP. Such experiences provoked a rescue of my memories as a player in theatrical experiences and impelled me to look for other languages to be worked in the school context. Therefore, this work represents my journey as a researcher of my own practice. The research aimed to inquire about the place of movement, play and theater games in Elementary School, observing the spaces / times granted to them and the possibilities of teaching performance through them. It is constituted as a qualitative research, of bibliographic character with field study. The main author studied is Viola Spolin (1987), creator of the theater games methodology. As a way of enriching the reflections, the work is also built based on Karine Ramaldi (2015; 2017), Robson Camargo (2017), Lucia Lombardi (2010; 2011), Joaquim Gama (2010), Alessandra Ancona de Faria (2002, 2010). On playing in childhood, the work is based on research by Tizuko Morchida Kishimoto, Gilles Brougère and Marcos Garcia Neira who study playing as a children's play culture. The work is divided into four chapters. The first chapter presents my memorial as a reflection on the paths that led me to the object of research. The second chapter presents the methodological procedures used, including the bibliographic survey. Chapter III, entitled “Theoretical framework”, presents the references that support the work and the reflection, the crossing of studies carried out on the subject and the definitions of concepts. Chapter IV deals with the analysis of experiences, experiences and reflections during my period as a teacher in elementary school that motivated the work, reflecting supported by the authors and by the questions that each of them generated in me. The results reveal that school spaces focused on art need to be occupied in order for movements and recreations to happen from within - from each player - and from outside - in every school environment.
About play and theater games in elementary school: movements from inside and outside
Keywords: Jogos teatrais; Theater games; Brincar; Play; Ensino fundamental; Elementary school; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO